Mobilizações científicas: provocações à docência - ROCHA, Luana Costa da (2022)
This work is presented in the structure of an academic portfolio and highlights the Scientific Mobilizations in order to carry out provocations regarding Teaching through the Mathematics Degree. In this writing are presented three scientific productions developed during my academic career, from 2016 to 2019, in the Mathematics Degree course, based on Resolution No. 5,044, of May 17, 2018, which approves the Project Proposal Pedagogical of the Mathematics Degree Course (PPP), of the Castanhal Campus, regarding the formulation of the Course Conclusion Work (CCW) in the publication mode. The first production exposes the perspective of teaching Ethnomathematics from an in locus investigation, which emphasizes the relationship of the individual with Mathematics and the influence that culture exerts. The second and third productions arise from reflections on the teach-learnteach mathematics in the degree course in mathematics. The elaboration of this work aimed at the interconnection of the contents of the scientific texts thinking about the constitution of the student-being and teacher-teaching, also seeking to resignificant the scientific productions presented in academic events in which Mathematics and Mathematics Education are discussed.